THE ROLE OF MOTIVATION IN THE MANAGEMENT PROCESS IN EFFECTIVELY ORGANIZING THE PRODUCTION PROCESS (International Conference on Modern Science and Scientific Studies, 2025)
This article examines the significant role of motivation in the management process for effectively organizing production processes. It analyzes the impact of motivation on employees’ performance, its place in the management process, and the motivation strategies applied in production processes. Additionally, the influence of motivation methods on productivity, quality, and overall efficiency in production processes is explored based on modern research and practical examples. The article serves as a valuable resource for specialists, managers, and researchers in the production sector.